PRIMING OF BRACHIARIA SEEDS WITH DIFFERENT SUGAR SOURCES AND CONCENTRATIONS - Batista, Thiago Barbosa [UNESP]; Cardoso Binotti, Eliana Duarte; Silva Binotti, Flavio Ferreira da; Sa, Marco Eustaquio de [UNESP]; Silva, Tiago Alexandre da [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2018)
Seed priming is a practice for improving the expression of seed physiological potential. Such technique consists of synchronizing and reducing the time of seed germination by controlled hydration. The aim of this study was to evaluate the effect of seed-priming with different sugar sources and concentrations on the physiological quality Urochloa brizantha seeds and initial seedling performance. Before treating, seeds were scarified chemically with concentrated sulphuric acid (H2SO4) for 5 minutes to overcome physical dormancy. The experimental design was completely randomized in a 3 x 6 factorial scheme consisting of priming using three sugar sources (glucose, sucrose, and maltose) and six concentrations (zero [water control], 2%, 5%, 10%, 15%, and 20%), with four replicates. The seeds were primed by direct immersion for 2 hours at 25 degrees C and, after hydration, they were dried for moisture equilibrium recovery. Seed germination, vigor, viability, and initial seedling growth were evaluated. The results showed that glucose was the source able to promote beneficial effects on the germination of U. brizantha cv. MG-5 seeds. Moreover, the supply of glucose at the concentrations of 2 and 5% for physiological conditioning increased seedling dry phytomass.
Keywords: Urochloa brizantha; Glucose Sucrose; Maltose; Direct immersion